An Explorative Study of Refugee Entrepreneurship and Startup Consulting in German-Speaking Europe: A Resource-Based Perspective - Andrew Isaak (European entrepreneurship research and practice: A multifaceted effort towards integration of different perspectives, 2020)
From the perspective of the resource-based view (Barney, 1991; Peteraf, 1993), this study presents a multi-level analysis of support structures from the current start-up consulting landscape for refugees in German-speaking Europe. Based on qualitative content analysis of 31 grant proposals submitted during a funding contest for refugee start-up consulting projects as well as over 30 interviews with participating refugee entrepreneurs, the study reveals the hurdles faced by refugee entrepreneurs, the unique resources they bring to the table and provides a snapshot of existing and planned support structures for refugee self-employment in the German-speaking realm. Incorporating extant literature on start-up consulting for refugees and migrants and classical evaluation criteria of business plan contests and incubators, common patterns are delineated. Consequent policy recommendations are highlighted and an integrated model for successful refugee start-up consulting is presented.
Keywords: L26; O52; M13; O15; J24; O35; 330; Refugee Entrepreneurship; Startup Incubators; Migration; Self-employment; Resource-Based View; Content Analysis; Consulting; Germany